2019
DOI: 10.1149/2.0941902jes
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Ionic Conductivity, Oxygen Transport and ORR with Structure of Dialkylacetamide-Based Electrolytes for Lithium-Air Batteries

Abstract: Chemical structures of lithium and tetrabutylammonium (TBA) salt solutions in N,N-dimethylacetamide (DMAc) and N,N-diethylacetamide (DEAc), two high Donor Number organic solvents, have been studied. In LiX salt solutions (where X = PF 6 − , CF 3 SO 3 − , ClO 4 − and NO 3 − ), solvation occurs when the Li + bonds with the solvent's carbonyl group forming Li + [O=C(CH 3 )N(CH 3 ) 2 ] n X − ion pairs. Infrared and 13 C-NMR spectra are consistent with the ion pair being solvent-separated when the anion is PF 6 − ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…These peaks disappeared after the cells were charged. A peak attributed to Li 2 CO 3 was also observed in the pattern for the sample discharged in the DMA‐based electrolyte, in agreement with previously reported results [19, 27, 28] …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These peaks disappeared after the cells were charged. A peak attributed to Li 2 CO 3 was also observed in the pattern for the sample discharged in the DMA‐based electrolyte, in agreement with previously reported results [19, 27, 28] …”
Section: Resultssupporting
confidence: 92%
“…A peak attributed to Li 2 CO 3 was also observed in the pattern for the sample discharged in the DMA-based electrolyte, in agreement with previously reported results. [19,27,28] The cathode surfaces after discharge were subsequently inspected by scanning electron microscopy (SEM). When a porous carbon electrode based on Ketjenblack (KB) was used, the Li 2 O 2 deposits could not be identified because the sizes of the single KB particles and the deposited Li 2 O 2 crystals were similar (Figure S5).…”
Section: Analysis Of the Discharge Processmentioning
confidence: 99%
“…Lithium ions are highly coordinated with four oxygens in DMSO solutions of LiPF 6 . This result is in agreement with the observation that lithium ion is solvated by four DMSO molecules forming Li + (DMSO) 4 PF -6 ion pair 117,118 . Yamada et al 10 have also shown, with Raman spectroscopy, the Li + (DMSO) 4 coordination in 1 mol•kg −1 solution, as can be seen in 3.11 (a).…”
Section: Structural Arrangementsupporting
confidence: 92%
“…Significant efforts have been focused on exploring the large design space of liquid electrolytes for improved operational temperature window, electrochemical stability, , ionic transport property, and the stability of electrode–electrolyte interfaces. , In particular, modifying liquid solvents using fluorination is considered one of the most convenient and scalable manufacturing methods. , The benefits of using the fluorinated solvents are three-fold. First, the fluorine substitution reduces the highest occupied molecular orbital (HOMO), which is necessary but not sufficient descriptor for the oxidative stability of the electrolyte. , The decreased HOMO level increases oxidation stability, , thus broadening the allowed open-circuit threshold for high-voltage cathodes. , Second, the simultaneous decrease in LUMO causes the fluorinated organic solvents to reduce before their nonfluorinated prototypes …”
mentioning
confidence: 99%